The Barometer INCODE as a self-assessment tool of innovation competencies - Mª Ángeles Andreu-Andrés; Juan A. Marin-García; Amparo García-Carbonell (Universitat Politècnica de València, 2017)
This study presents the research results of the  opinions  analysis  of  the  participants in a MOOC (Massive Open Online Course) on  the  diagnosis  of  innovation  skills  for improving  processes.  Participants use the INCODE   Barometer   for   self-assessment and, post-treatment, they provide their opinions about the instrument.  Research questions  inquiry  whether  the  Barometer identifies    innovation    competencies    of participants  and  if  it  could  be  used  at enterprise  level.  Results of a qualitative analysis about the participants' reflections illustrate that the assessment tool has helped them to identify their innovation skills,      strengths      and      weaknesses, although a more reliable results would be accompanied by additional evaluations. As company managers, participants would not opt for the INCODE Barometer as the only tool  in  selecting,  training  and  developing teams,  although  they  consider  its  validity. Difficulties in using the Barometer are due to the lack of experience in the situations to be judged by the survey respondents, and the difficulty of being totally objective in   assessing   their   own   behaviors.   The results  obtained,  along  with  other  own studies, together with companies involved in  the  project  and  the  literature  review in  the  field  will  enable  to  step  forward from   the   INCODE   Barometer   to   the FINCODA  Barometer,  a  key  objective  of  a new  European  project.  The  new  tool  will facilitate  both  training  and  evaluation  of innovation  behaviors  in  higher  education and companies.